Pemanfaatan Inovasi dengan Adopsi Structural Equation Model (SEM) Untuk Pengembangan Model Keberlanjutan Agribisnis Padi Organik - Nainggolan, Mai Fernando; Tambunan, Herlina Yolanda; Ismail, Agus Yadi; Sembiring, Surya Abadi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The efficiency of rice farming and increasing farmers' income requires new innovations to be developed in society, such as organic-based farming. Based on this, for the development of sustainable organic rice agribusiness, it is necessary to build a Sustainable Organic Rice Agribusiness Model through a systems approach based on a strategic approach to each subsystem which includes input subsystem, farming subsystem, handling/processing and marketing subsystem, as well as supporting subsystems to achieve objectives. The development of organic rice agribusiness can be achieved more effectively and optimally to increase food security while supporting sustainable agriculture. Analysis of the performance of the agribusiness system and the sustainability of organic rice agribusiness is carried out using descriptive methods which are applied to describe the characteristics of farmers and the performance of each subsystem in the organic rice agribusiness system. Structural Equation Model (SEM) analysis was used to answer the research objectives. The calculation results show that the GoF value is 0.75. The level of sustainability of Pangandaran organic rice agribusiness obtained an average total percentage score of 62.85%, this means that the level of sustainability of rice agribusiness is quite good.